Idiopathic mitral valve prolapse with tricuspid, aortic and pulmonary valve involvement: An autopsy case report - Heena M Desai; Gayathri P Amonkar (Wolters Kluwer Medknow Publications, 2015)
Mitral valve prolapse (MVP) is usually asymptomatic, but can be associated with complications such as infective endocarditis, mitral regurgitation, thromboembolism and sudden cardiac death. It has been very rarely reported to occur in association with other valvular involvement. A 55-year-old male patient was brought dead and at autopsy the mitral valve orifice was stenotic and the leaflets were enlarged, myxoid and bulging suggestive of MVP and chordae tendinae were thickened, stretched and elongated. Similar changes were seen in the tricuspid valve. The pulmonary and aortic valves also showed myxomatous degeneration of their cusps. Myxomatous degeneration is the most common cause of MVP and it can be associated with involvement of the other valves. Concomitant involvement of the aortic valve has been reported, however it is very rare and simultaneous involvement of the pulmonary valve has not been reported in the literature so far. We report a case of MVP associated with myxomatous degeneration of the tricuspid, pulmonary and aortic valves.